A computer simulation of the effect of dusty particles on the characteristic of RF discharges - Kravchenko, O.Yu.; Vakulenko, A.V.; Lisitchenko, T.E.; Levada, G.I.; Yastrub, Yu.A. (Вопросы атомной науки и техники, 2007)
We are carried out the computer simulation of the dust cloud dynamics in the radio frequency (RF) discharges at the microgravity conditions using PIC/MCC method for electrons and ions and hydrodynamics model for dust particles. The moving of dust particles is governed by the electrostatic force, ion and neutral drag forces, which are averaged over period of RF discharge. The obtained results show that dust particles form layer with sharp boundaries in the discharge chamber. Locations of the layer boundaries don't coincide with the edges of the rf-sheathes and depend on size of dust particles and ion density in discharge.